Research work on informational demands of scientific workers and specialists of other branches in the Lithuanian SSR: the main tendencies, methods, and results - Krominaitė, Lolita (Knygotyra, 1988)
In Lithuania, as well as in the Soviet Union, research work on informational demands began in the mid-seventies. Over two decades of research on this problem, the professional informational demands of scientific workers and specialists in other fields—such as farming, medicine, chemistry, and technology—were investigated. The research survey of informational demands of scientific workers and other specialists has shown a rise in the level of research work in our republic since the beginning of the 1980s, as well as the mistakes and gaps in problem investigation. Specifically, informational professional demands have not been equally well investigated across all branches of science. The specific characteristics of informational demands of philologists have not been conveyed, and the demands of scientific workers for self-education have not been thoroughly examined.